2001
DOI: 10.1093/emboj/20.8.1829
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structures of complexes of the small ribosomal subunit with tetracycline, edeine and IF3

Abstract: The small ribosomal subunit is responsible for the decoding of genetic information and plays a key role in the initiation of protein synthesis. We analyzed by X-ray crystallography the structures of three different complexes of the small ribosomal subunit of Thermus thermophilus with the A-site inhibitor tetracycline, the universal initiation inhibitor edeine and the C-terminal domain of the translation initiation factor IF3. The crystal structure analysis of the complex with tetracycline revealed the function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
466
4
11

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 492 publications
(507 citation statements)
references
References 69 publications
26
466
4
11
Order By: Relevance
“…24,25 These studies suggest that the 970 loop plays an important role in protein synthesis. This notion is supported by structural studies showing that the 970 loop forms part of the primary binding site for tetracycline 26,27 and by the isolation of a tetracycline-resistant strain of Helicobacter pylori that contains three mutations at positions 965, 966 and 967. 28 Here, we identify the sequence and structural motifs of the 970 loop nucleotides that are essential for ribosome function in bacteria and propose a model for the role of the 970 loop in protein synthesis.…”
Section: Introductionmentioning
confidence: 89%
“…24,25 These studies suggest that the 970 loop plays an important role in protein synthesis. This notion is supported by structural studies showing that the 970 loop forms part of the primary binding site for tetracycline 26,27 and by the isolation of a tetracycline-resistant strain of Helicobacter pylori that contains three mutations at positions 965, 966 and 967. 28 Here, we identify the sequence and structural motifs of the 970 loop nucleotides that are essential for ribosome function in bacteria and propose a model for the role of the 970 loop in protein synthesis.…”
Section: Introductionmentioning
confidence: 89%
“…In bacteria, edeine binds between the P-site and the E-site of the small subunit and impairs the binding of initiator tRNA to the P-site during initiation 32,33 . In the yeast ribosome, edeine binds to the same region but adopts a markedly different conformation than on the bacterial 30S subunit (Fig.…”
Section: Research Articlementioning
confidence: 99%
“…The mismatch regions of the 50S subunit are distributed around its periphery, primarily associated with its proteins. None of the matching RNA regions participate in ligand interactions in the 30S subunit, but many of these helices in the 50S (Pioletti et al 2001;Yusupov et al 2001;Klaholz et al 2003;Rawat et al 2003) and regions found to be flexible in comparative structural studies (see Matadeen et al 1999;Yusupov et al 2001;Ogle et al 2002;Klaholz et al 2003;Rawat et al 2003) mapped into crystal structures of the 30S subunit (PDB identification: 1GIX; Yusupov et al 2001). (D) Secondary structure diagram of the 23S RNA, 5S RNA, and associated proteins, colored in dark gold if data available for the region generally were in good agreement (<25% of mismatch); blue, >25% of mismatches; and gray, no data in our data set.…”
Section: Distribution Of Mismatchesmentioning
confidence: 99%